Time‐frequency comovement among green financial assets and cryptocurrency uncertainties. (19th December 2022) - Haq, Inzamam Ul
Abstract: The high energy consumption and carbon footprints have raised environmental and sustainable concerns of green investors and policymakers. This study explores comovements between three green and socially responsible financial assets, S&P global clean energy index (GCEI), S&P green bonds index (GB), DJ sustainability world index (DJSWI) and four cryptocurrency uncertainty/attention indices cryptocurrency policy uncertainty index, Central Bank Digital Currencies Uncertainty Index, Central Bank Digital Currencies Attentions Index and Index of Cryptocurrency Environmental Attention using the bivariate wavelet coherence approach. The findings show that GCEI, GB, DJSWI returns have consistent positive comovement with all cryptocurrency uncertainty/attention indices in the medium‐term, suggesting their time‐varying leading role. Evidence of negative coherences shows that higher cryptocurrency uncertainties/attentions lead to lower green financial asset returns, reflecting the adverse impact of higher uncertainties/attention on the trust of green and sustainable investors. The above empirical findings offer up‐to‐date insights for guiding policymakers, and regulators, enabling them in environmental policy development. Furthermore, socially responsible investors can make better investment judgments by considering the environmental concerns in the cryptocurrency marketplaces.